1996
DOI: 10.1095/biolreprod55.6.1419
|View full text |Cite
|
Sign up to set email alerts
|

Follicular 3β-hydroxysteroid Dehydrogenase and Cytochromes P450 17α-hydroxylase and Aromatase Messenger Ribonucleic Acids in Cattle Undergoing Superovulation1

Abstract: In this study, we tested the hypothesis that there is altered abundance of transcripts of genes coding for the enzymes cytochrome P450 17 alpha-hydroxylase (P450(17 alpha)), cytochrome P450 aromatase (P450arom), and 3 beta-hydroxysteroid dehydrogenase (3 beta-HSD) in follicles of cattle hyperstimulated with eCG compared to FSH. Treatments were initiated on Day 10 of the cycle, and all cows received prostaglandin (PG) on Day 12. In experiment 1, blood samples were taken to determine plasma progesterone and estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
1
14
0
3
Order By: Relevance
“…The multiple FSH injections followed by a coasting period and an LH injection have been reported to generate developmentally competent oocytes and good to high embryonic developmental rates (Blondin et al 2002, Chaubal et al 2007, Knijn et al 2011. Although some differences in gene expression compared with natural cycles are expected, it has been demonstrated that stimulation with FSH, compared with those performed with eCG, has a profile of 17b-estradiol similar to those observed in a natural cycle (Soumano et al 1996, Knijn et al 2011). However, little was previously known about the gene expression cascade that follows the LH surge and the molecular determinants involved in ovulation and the last stage of GC differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…The multiple FSH injections followed by a coasting period and an LH injection have been reported to generate developmentally competent oocytes and good to high embryonic developmental rates (Blondin et al 2002, Chaubal et al 2007, Knijn et al 2011. Although some differences in gene expression compared with natural cycles are expected, it has been demonstrated that stimulation with FSH, compared with those performed with eCG, has a profile of 17b-estradiol similar to those observed in a natural cycle (Soumano et al 1996, Knijn et al 2011). However, little was previously known about the gene expression cascade that follows the LH surge and the molecular determinants involved in ovulation and the last stage of GC differentiation.…”
Section: Discussionmentioning
confidence: 98%
“…The bovine Cyp19 cDNA probe was prepared in our laboratory (Soumano et al 1996) and encompasses the entire haeme-binding and I-helix regions. The bovine Cyp11a cDNA was a gift from Dr M R Waterman (Vanderbilt University School of Medicine, Nashville, TN, USA) and encompasses the complete coding sequence (John et al 1984).…”
Section: Northern Hybridizationmentioning
confidence: 99%
“…The bovine P450arom cDNA probe was prepared in our laboratory (Soumano et al 1996), and encompasses the region coding for the entire heme-binding and I-helix regions. The probe is specific for oestrogen-secreting tissues, and hybridizes to three bands of follicular total RNA at 6·5, 3·4 and 1·8 kb, of which only the 6·5 kb transcript is polyadenylated.…”
Section: Hybridizationmentioning
confidence: 99%